2019
DOI: 10.1093/jscr/rjy356
|View full text |Cite
|
Sign up to set email alerts
|

Madelung’s disease: long-term follow-up

Abstract: Madelung’s disease (MD) is a rare lipid metabolic disorder of adipose tissue overgrowth, which has been reported to be related to alcohol abuse. Although it does not affect survival itself, alcoholism and metabolic disorders associated with MD can be life-threatening. Although surgical procedures and classifications have been reported, long-term follow-up has rarely been reported. Here, we report a 61-year-old Japanese man with MD who has been followed-up for 12 years. Lipectomy was performed three times over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…We found no clear evidence that BSA directly impacts life expectancy, but long-term follow-up studies showed high rates of incidences of somatic neuropathy and sudden death due to fat occupation in the mediastinal space [30,31]. In a 12-year follow-up study of one patient, Suito et al reported death from hemorrhagic shock due to hepatocellular carcinoma and hepatorenal syndrome, although they found no recurrence of fat masses [32].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…We found no clear evidence that BSA directly impacts life expectancy, but long-term follow-up studies showed high rates of incidences of somatic neuropathy and sudden death due to fat occupation in the mediastinal space [30,31]. In a 12-year follow-up study of one patient, Suito et al reported death from hemorrhagic shock due to hepatocellular carcinoma and hepatorenal syndrome, although they found no recurrence of fat masses [32].…”
Section: Introductionmentioning
confidence: 67%
“…BSA can be associated with neuropathies; myopathies; reduced deep tendon reflexes; paresthesia; hypothalamic and pituitary lesions; neuroendocrine syndromes; sudden death; autonomous nervous system dysfunctions; myoclonic epilepsy with ragged red fibers (MERRF); and carotid compression [11,17,[32][33][34][35]. Other associated manifestations include liver failure; metabolic syndrome; altered glucose tolerance; dyslipidemia; lipodystrophy; and obesity-most patients are overweight, while around 10% of the cases have normal weight [25][26][27]32,33]. Hypercholesterolemia, hypothyroidism, and hyperinsulinemia and insulin resistance, (comorbidities often found in BSA patients), suggest a possible link to metabolic diseases [27,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with Madelung’s disease need long-term observation and multidisciplinary systemic management of comorbidities[ 27 ]. It is also important to observe these patients due to disease relapse, the need for re-operation, and possible liposarcoma by ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…The morphologic features of this patient's mass corresponded to type Ib, based on the presence of a mass in the posterior neck region and both shoulders [26] ( Table 2). The direction in which adipose tissue spreads is not yet clear [27]. Frequently, lipoma distribution around neck occurs in patients with MSL.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that MSL is directly related to life expectancy is not clear, but a long term follow-up study showed incidences of somatic neuropathy and sudden death due to fat occupation in mediastinal space [31]. Motomu et al's 12-year follow-up study of one patient found no recurrence of mass, but the patient died of hemorrhagic shock due to hepatocellular carcinoma and hepatorenal syndrome [27]. Fonseca et al reported the presence of neuropathy in about 85% of patients with MSL and an association with sudden cardiac death [17].…”
Section: Discussionmentioning
confidence: 99%